2020
DOI: 10.9734/ajfar/2020/v6i230093
|View full text |Cite
|
Sign up to set email alerts
|

Macrozoobenthos Spatial Distribution as the Indicator of Cikeruh River Pollution in Sumedang Regency, West Java

Abstract: Cikeruh River is one of the tributaries of the Citarum River which has received a variety of inputs, which can affect the river water quality and cause pollution. Macrozoobenthos is an organism that can determine the pollution of waters. This research aims to determine the spatial distribution of macrozoobenthos communities in the Cikeruh River as the indicator of pollution. This research was conducted in July 2019 - August 2019 using the field survey method. The data collection technique used is purposive sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
3
Order By: Relevance
“…Tarebia granifera y M. tuberculata (pertenecientes a la familia Thiaridae) son originarias de Asia y África respectivamente (Lutfi et al, 2020). Fueron observados por primera vez en Cuba a finales del siglo pasado (Gutiérrez et al, 1997) y desde entonces han sufrido una amplia expansión en ríos y estanques de todo el país.…”
Section: Gasterópodos Fluvialesunclassified
See 1 more Smart Citation
“…Tarebia granifera y M. tuberculata (pertenecientes a la familia Thiaridae) son originarias de Asia y África respectivamente (Lutfi et al, 2020). Fueron observados por primera vez en Cuba a finales del siglo pasado (Gutiérrez et al, 1997) y desde entonces han sufrido una amplia expansión en ríos y estanques de todo el país.…”
Section: Gasterópodos Fluvialesunclassified
“…Las variables ambientales pueden influir en las oscilaciones poblacionales de la fauna malacológica, y por tanto en la incidencia de las enfermedades transmitidas por moluscos (Fimia et al, 2014a,b;Fimia et al, 2015a,b;Fimia et al, 2016a,b;Osés et al, 2017;Zdelar et al, 2018;Albarrán-Mélzer et al, 2019;Lutfi et al, 2020;Sun et al, 2020). En la actualidad, cobran un gran auge e importancia los estudios relacionados con la modelación matemática y la confección de modelos de pronósticos de alerta temprana (Fimia et al, 2012;Fimia et al, 2015b;Castillo et al, 2016;Fimia et al, 2016a;Osés et al, 2017) debido a los efectos del cambio climático.…”
Section: Introductionunclassified
“…The habitats of this species are rivers or lakes with calm or swift currents. Previous research found that Sulcospira testudinaria was present in the Cikeruh River [Lutfi et al, 2020], Code River [Hellen et al, 2020], Meru Betiri National Park [Suratno et al, 2020], Gunung Kidul [Isnaningsih and Listiawan, 2010], and the Brantas River [Febbyanto et al, 2015]. This species was used as a bioindicator for aquatic environmental health [Hertika et al, 2021], and was used to measure the results of efforts to reduce levels of organic matter in aquaculture wastewater [Lailiyah et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
“…Los conocimientos de sistemática y taxonomía de las especies involucradas son indispensables para una certera identificación (Vazquez & Gutiérrez, 2007;Vázquez & Cobian, 2014;Vázquez & Sánchez, 2015;Castillo et al, 2016) ya que diferentes grupos taxonómicos transmiten diferentes enfermedades parasitarias. Las variables ambientales pueden influir en las oscilaciones poblacionales de la fauna malacológica, y por tanto en la incidencia de las enfermedades transmitidas por moluscos (Fimia et al, 2014a, b;Fimia et al, 2015a, b;Fimia et al, 2016a, b;Osés et al, 2017;Zdelar et al, 2018;Albarrán-Mélzer et al, 2019;Lutfi et al, 2020;Sun et al, 2020). En la actualidad, cobran un gran auge e importancia los estudios relacionados con la modelación matemática y la confección de modelos de pronósticos de alerta temprana (Fimia et al, 2012;Fimia et al, 2015b;Castillo et al, 2016;Fimia et al, 2016a;Osés et al, 2017) debido a los efectos del cambio climático.…”
Section: Introductionunclassified